2012
DOI: 10.1073/pnas.1121528109
|View full text |Cite
|
Sign up to set email alerts
|

An essential bacterial-type cardiolipin synthase mediates cardiolipin formation in a eukaryote

Abstract: Cardiolipin is important for bacterial and mitochondrial stability and function. The final step in cardiolipin biosynthesis is catalyzed by cardiolipin synthase and differs mechanistically between prokaryotes and eukaryotes. To study the importance of cardiolipin synthesis for mitochondrial integrity, membrane protein complex formation, and cell proliferation in the human and animal pathogenic protozoan parasite, Trypanosoma brucei , we generated conditional cardiolipin synthase-knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 66 publications
(71 reference statements)
5
70
0
Order By: Relevance
“…A bacterial-type CL synthase is also present in some unicellular eukaryotes [22]. Not surprisingly, the CL pathway is regulated by PGC-1, the transcription factor that controls the biogenesis of mitochondria [23].…”
Section: Biosynthesis Of CLmentioning
confidence: 99%
“…A bacterial-type CL synthase is also present in some unicellular eukaryotes [22]. Not surprisingly, the CL pathway is regulated by PGC-1, the transcription factor that controls the biogenesis of mitochondria [23].…”
Section: Biosynthesis Of CLmentioning
confidence: 99%
“…Low levels of PG and CL have been demonstrated in T. brucei procyclic and bloodstream forms [137, 149] and Leishmania [151, 158, 229]. Very recently, a protein homologous to PGP synthase from mammalian cells and yeast has been identified and experimentally characterized in T. brucei [266].…”
Section: Phospholipid Synthesismentioning
confidence: 99%
“…Surprisingly, CL synthase in T. brucei was found to contain the characteristic prokaryotic-type, rather than eukaryotic-type, CL synthase motif consisting of two phospholipase D domains [149, 180]. Conditional gene knock-out of T. brucei CL synthase in procyclic forms demonstrated that it is essential for parasite survival in culture [149].…”
Section: Phospholipid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, a similar mechanism during secondary and, probably, tertiary endosymbiotic events within Archaeplastida gave rise to a third pathway where both enzymes were replaced by PLD-enzymes. Experimental evidence has shown the presence of CL in several members of the Alveolata (Apicomplexa) and Excavate (Kinetoplastid) groups [34,35]. In these organisms CL is present at low levels, which could be due to the presence of a pure PLD pathway.…”
Section: A New Model For CL Evolutionmentioning
confidence: 97%